The effect of Cellulases and Xylanases on the in vitro digestibility of Asparagus browse (Asparagus officinalis), Corn stover (Zea mays) and Peanut hulls (Arachis hypogaea) in ruminants - Macías-Rodríguez, Edis Geovanny; Gómez-Bravo, Carlos Alfredo; Álava-Moreira, Jimmy Roberto; Hurtado, Ernesto Antonio (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
Crop residues play an important role in animal production worldwide. Improving the nutritional potential of low-quality options with fibrolytic enzymes would improve forage digestibility and utilization. Using an in vitro method, it was evaluated the effect of Cellulases (EC: 3.2.1.4) and Xylanases (EC: 3.2.1.8) applied at 4 levels: 0 (control), 2,000; 4,000 and 8,000 UI·kg-1 MS in Corn stover (CS), Asparagus browse (AB) and Peanut hulls (PH). When applying Cellulases to CS, the in vitro digestibility of dry matter (IVDMD) and the in vitro digestibility of neutral detergent fiber (IVNDFD) were higher (P<0.001) than the control group (63.7 vs. for 61.8% and 51.9 vs. 50.1%). Similar effects were found with Xylanases (64.1 vs. for 61.8% and 53.0 vs. 51.6%). The IVDMD and IVNDFD of AB were not affected by the application of Cellulases or Xylanases. In the case of PH, the application of Cellulases or Xylanases improved the IVDMD (24.9 vs. 22.3% and 24.6 vs. 22.3%), but not the IVNDFD. Also, the in vitro gas production at 48 hours was not influenced by the type of enzymes or by their levels of application to the residues evaluated. Cellulases or Xylanases applied to CS and AB had no effect on the concentration of tVFA (acetic acid + propionic acid + butyric acid). In the case of PH, the concentration of tVFA was similar between the control and those treated with Cellulases, while the application of Xylanases resulted in lower concentrations of tVFA than the control. Cellulases and Xylanases influenced IVDMD, IVNDFD and the concentration of tVFA depending on the substrate used.